Theory of Industrial Disputes - Turner, Alan (Review of Economic Studies, 1934)
Theory of Industrial Disputes Get access Alan Turner Alan Turner Nottingham Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 2, February 1934, Pages 154–156, https://doi.org/10.2307/2967625 Published: 01 February 1934